Selectively Enhanced Motion Perception in Core Video Gamers. (June 2013) - Hutchinson, Claire V; Stocks, Rachel
In this study we examined the effects of action video game play on performance for encoding global motion. There were no significant differences between video game player (VGP) and non-video game player (NVGP) performance for either translational or rotational motion. For radial motion, VGPs were significantly better than NVGPs at discriminating contracting, but not expanding, elements. We postulate that VGPs are selectively sensitive to radial contractions because, while this type of optic flow information is abundant in action video games, it is not encountered in abundance in the real world.